Does Trait Hostility Moderate the Asymmetry in Victim-Perpetrator Perceptions of Aggressive Behaviors?. Issue 2 (April 2022) - McCarthy, Randy J.; Rivers, Alison K.
Victims often perceive aggressive behaviors as being more harmful than do perpetrators—a so-called victim-perpetrator asymmetry. We examined whether this victim-perpetrator asymmetry was especially strong for individuals who were high in trait hostility. In two studies—one where participants recalled actual aggressive experiences and one where participants took the perspective of a person in a vignette—we found that victims who were high in trait hostility, relative to those who were low, viewed aggressive behaviors as being most harmful. We found somewhat inconsistent effects for whether perpetrators viewed the aggressive behaviors as more justified than victims did and whether trait hostility moderated this judgment. Collectively, the current findings show that victims who are high in trait hostility are especially likely to view an aggressive behavior as harmful, which potentially makes conflict resolution difficult for these individuals and increases the likelihood they would retaliate.